Методика розрахунку експериментального зразка струминного гомогенізатора молока - Кюрчев, Сергій Володимирович; Самойчук, Кирило Олегович; Ломейко, Олександр Петрович; Kiurchev, Serhii; Samoichuk, Kyryl; Lomeiko, Oleksandr (Запоріжжя : ТДАТУ, 2023)
UA: Для розробки та досліджень нових типів гомогенізаторів, а також теорій диспергування та гомогенізації мікроемульсій важливим етапом є розробка методики розрахунку експериментального зразка дослідного гомогенізатора. Але основною проблемою при проведенні досліджень струминних гомогенізаторів є відсутність єдиної теорії, та, як наслідок, методики розрахунку таких машин. Тому мета даної статті – розробити методику розрахунку експериментального зразка струминного гомогенізатора молока. В результаті проведених досліджень розроблена установка, призначена для проведення експериментальних досліджень процесу струминного диспергування молочної емульсії. Приведено методику та здійснені основні розрахунки експериментального зразка струминного гомогенізатора. Наведені формули для визначення продуктивності, потужності приводу вершків та знежиреного молока, розміри камери гомогенізатора, параметри трубопроводів в залежності від необхідного розміру жирових кульок. Проведені дослідження дають можливість розробити конструкції гомогенізаторів та диспергаторів, енергоефективність яких значно перевищує існуючі. EN: For the development and research of new types of homogenizers, as well as the theories of dispersion and homogenization of microemulsions, an important stage is the development of a methodology for calculating an experimental sample of an experimental homogenizer. But the main problem in conducting research on jet homogenizers is the lack of a single theory, and, as a result, the methodology for calculating such machines. Therefore, the purpose of this article is to develop a methodology for calculating an experimental sample of a jet milk homogenizer. As a result of the conducted research, an installation designed for conducting experimental studies of the process of jet dispersion of milk emulsion was developed. The description of the principle of action of the homogenizer, which is based on the introduction of a thin stream of cream into a high- speed flow of skimmed milk, is given. Its technical characteristics are calculated. The methodology and basic calculations of the experimental sample of the jet homogenizer are given. Formulas for determining productivity, cream and skimmed milk drive power, homogenizer chamber dimensions, pipeline parameters depending on the required size of fat balls are given. The total maximum power consumption of the experimental sample of the homogenizer is about 1.4 kW. The conducted research makes it possible to develop the designs of homogenizers and dispersers, the energy efficiency of which significantly exceeds the existing ones. And not only in food and processing, but also in chemical, pharmaceutical, agricultural and many other industries. The developed method of calculating the homogenizer due to increased energy efficiency will be in demand by enterprises producing equipment for the food industry.
Calculation methodology of the experimental sample of the stream milk homogenizer
Кюрчев С. В., Самойчук К. О., Ломейко О. П. Методика розрахунку експериментального зразка струминного гомогенізатора молока. Науковий вісник Таврійського державного агротехнологічного університету : електронне наукове фахове видання. Запоріжжя : ТДАТУ. 2023. Вип. 13, том 1. C. 8-19.
Keywords: гомогенізація; диспергування молока; струминний гомогенізатор; експериментальний зразок; розрахунок; homogenization; dispersion of milk; jet homogenizer; experimental sample; calculation